2023
DOI: 10.1007/s00431-023-04971-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of levosimendan as treatment option in a large case-series of preterm infants with cardiac dysfunction and pulmonary hypertension

Abstract: Levosimendan as a calcium-sensitizer is a promising innovative therapeutical option for the treatment of severe cardiac dysfunction (CD) and pulmonary hypertension (PH) in preterm infants, but no data are available analyzing levosimendan in cohorts of preterm infants. The design/setting of the evaluation is in a large case-series of preterm infants with CD and PH. Data of all preterm infants (gestational age (GA) < 37 weeks) with levosimendan treatment and CD and/or PH in the echocardiographic assessment be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We could demonstrate that recipient and donor twins frequently present a need for iNO treatment due to early PH, and second-and third-line drugs such as sildenafil (i.v./orally) might be useful in selected cases with severe PH and without a response to iNO treatment. The association of levosimendan treatment with improvements in PH and CD severity in preterm and term infants was demonstrated in two previous studies from our group [26,27]. The calcium sensitizer levosimendan has the pharmacological potential to positively influence pulmonary vascular resistance by the following mechanisms: (a) calcium sensitization with a lusitropic/inotropic/vasodilating effect, (b) phosphodiesterase-3 inhibition, and (c) the vasodilation of smooth muscle cells by affecting ATP-depending potassium channels.…”
Section: Postnatal Management Of Ph and CD In Neonates Following Comp...mentioning
confidence: 58%
See 3 more Smart Citations
“…We could demonstrate that recipient and donor twins frequently present a need for iNO treatment due to early PH, and second-and third-line drugs such as sildenafil (i.v./orally) might be useful in selected cases with severe PH and without a response to iNO treatment. The association of levosimendan treatment with improvements in PH and CD severity in preterm and term infants was demonstrated in two previous studies from our group [26,27]. The calcium sensitizer levosimendan has the pharmacological potential to positively influence pulmonary vascular resistance by the following mechanisms: (a) calcium sensitization with a lusitropic/inotropic/vasodilating effect, (b) phosphodiesterase-3 inhibition, and (c) the vasodilation of smooth muscle cells by affecting ATP-depending potassium channels.…”
Section: Postnatal Management Of Ph and CD In Neonates Following Comp...mentioning
confidence: 58%
“…Postnatal treatment with vasoactive drugs was due to the decision of the attending physician, according to in-hospital standards of clinical management. The echocardiographic assessment of PH or right-, left-, or bi-ventricular dysfunction (RVD, LVD, BVD) used in our department was described previously [25,27]. For the present study, the echocardiographic diagnostic reports of the attending physicians were retrospectively reviewed, and PH (moderate to severe), any cardiac dysfunction (CD), and subclassification into RVD/LVD/BVD were stated as present or not present according to the documented report/echocardiographic exam.…”
Section: Echocardiographic Assessment and Vasoactive Drug Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also suggested that LEVO may have advantages over MIL in terms of the dosing regimen [36,182]. Ten years later, a large case-series study of preterm infants (n = 105, GA < 37 weeks) with severe cardiac dysfunction and pulmonary hypertension demonstrated that LEVO treatment was associated with a rapid improvement in hemodynamic derangement [184]. Relevant systematic reviews have reported controversial results.…”
Section: Levosimendanmentioning
confidence: 99%